THE EFFECT OF PLANTING PATTERNS AND TIMING OF RICE VARIETIES ON GRAIN YIELD (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
When calculating the yield of rice, it was determined that the yield increased by 3.3-5.9 t/ha in the variant of the planting scheme with a planting rate of 999 thousand seedlings per hectare in the 30x10x3 scheme. Experimental data showed that from the seedling stage to the ripening stage, the stem height and root length of the plant developed rapidly, and the accumulation of dry mass was also observed to vary according to each planting scheme and timing. In the studies, there was no significant difference between the planting dates. However, differences were noted in the planting schemes and the number of seedlings per 1m2.